IMPACT OF BRAND IMAGE ON CUSTOMER LOYALTY WITH THE MEDIATING ROLE OF CUSTOMER SATISFACTION AND BRAND AWARENESS - Abbas, Umair; Islam, K. M. Anwarul; Hussain, Sajid; Baqir, Muhammad; Muhammad, Noor (International Journal of Marketing Research Innovation, 2021)
The study indicates the impact of Brand Image on Customer Loyalty with the Mediating Role of Customer satisfaction and Brand Awareness. A questionnaire is filled by the 300 respondents that are selected through non-probability to measure customer satisfaction and their loyalty to their favorite Brand. The respondent filed the questionnaire according to their favorite brand. In the study 22 statements and 5 points, Likert Scaled survey questionnaire was filled by the 300 respondents. The results were made by using different methods. The result is based on the statistics test which displays that the Image of the brand and customer Loyalty is very significant with Customer Satisfaction and Brand Awareness, but Brand Image is insignificant with Brand Awareness. The result is analyzed through SPSS software for statistical analysis. The study was conducted within a short time and within the limited resources due to the pandemic attack of the COVID-19. In the future study, the major topic is recommended due to the current situation in the world due to the pandemic attack of the COVID-19 impact of any pandemic diseases on customer loyalty. JEL Classification Codes: M31, M39.